Production of Insect Toxin Beauvericin from Entomopathogenic Fungi Cordyceps militaris by Heterologous Expression of Global Regulator - Rina Rachmawati; Hiroshi Kinoshita; Takuya Nihira (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Cordyceps militaris is one of entomopathogenic fungi species that is well known to be a traditional medicine in China for decades. Although the pharmaceutical and/or toxic properties of C. militaris has attracted attention as a promising resource for finding bioactive compounds, only a few substances including cordycepin have been reported so far. In the previous report heterologous expression of LaeA, a global regulator for secondary metabolites production in fungi, has been succeeded in C. militaris. The LaeA-engineered transformants are proved to produce new and/or elevated production of secondary metabolites, as detected by HPLC analysis. In order to further characterize the secondary metabolites that were being significantly produced by LaeA transformant, HPLC profiling and structure elucidation by proton NMR were conducted in two target compounds, designated as compound 1 and compound 2. Compound 1 possessed the highly similar characters to insect toxin beauvericin in UV spectrum, molecular weight, and retention time in HPLC analysis. Proton NMR analysis revealed that compound 1 had the same proton signals as beauvericin.